2019
DOI: 10.5603/dk.2019.0016
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics and smectite absorbent gel formulation reduce liver stiffness, transaminase and cytokine levels in NAFLD associated with type 2 diabetes: a randomized clinical study

Abstract: Introduction. In double-blind single center randomized clinical trial (RCT), the efficacy of alive probiotics supplementation with smectite gel vs. placebo in type 2 diabetes patient with non-alcoholic fatty liver disease (NAFLD) detected on ultrasonography (US) were studied. Material and methods. A total of 50 patients met the criteria for inclusion. They were randomly assigned to receive Symbiter Forte combination of probiotic biomass with smectite gel (250 mg) or placebo for 8-weeks. The primary main outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…Therapy is mainly based on lifestyle changes to reduce body weight [7], and in some cases the use of metformin, glitazones, hypolipidemic drugs and TNF-a antagonists required to treat concomitant conditions [7,8]. In addition, recent studies have shown that the use of omega-3 polyunsaturated fatty acids (PUFA) can reduce liver fat content [9,10], while antioxidants [11][12][13] and probiotics [14][15][16][17] may have anti-inflammatory properties.…”
Section: Introductionmentioning
confidence: 99%
“…Therapy is mainly based on lifestyle changes to reduce body weight [7], and in some cases the use of metformin, glitazones, hypolipidemic drugs and TNF-a antagonists required to treat concomitant conditions [7,8]. In addition, recent studies have shown that the use of omega-3 polyunsaturated fatty acids (PUFA) can reduce liver fat content [9,10], while antioxidants [11][12][13] and probiotics [14][15][16][17] may have anti-inflammatory properties.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, another group reported a near 33% reduction in the marker from baseline, a change that was also found to be significant compared to control ( 129 ). Through a series of four studies, Kobyliak et al ( 136 139 ) have reported significant changes of –5.81 ± 9.13, –7.95 ± 1.27, –5.02 ± 9.33, and –6.75 ± 7.73 pg/mL in TNF- α from baseline compared to control following multi-species probiotic supplementation.…”
Section: Resultsmentioning
confidence: 99%
“…By contrast, unsaturated fats reduce the risk of chronic diseases. Human studies have shown that a high-fat diet increases the abundance of total anaerobic microorganisms as well as levels of Bacteroides [67][68][69] .…”
Section: Dysbiosis and Diabetes: The Influence Of Dietmentioning
confidence: 99%